1994
DOI: 10.1177/104063879400600216
|View full text |Cite
|
Sign up to set email alerts
|

The Cytology of Squamous Cell Carcinomas in Domestic Animals

Abstract: Abstract. A series of 40 tumors with a proven diagnosis of squamous cell carcinoma for which both histology and cytology were available were classified according to their histologic appearance as well differentiated, moderately differentiated, and poorly differentiated. The Romanowsky-stained cytology specimens were reviewed. When available, Papanicolaou-stained smears were included. The cytologic findings for each of the 3 groups are described, and the most significant findings are photographically illustrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 5 publications
3
13
0
Order By: Relevance
“…In our study, equine goblet cells were easily identified with ICS but not with CBS mirroring a previous study where few goblet cells were found with CBS and routine staining [1]. The main focus of equine conjunctival cytology is to detect and classify inflammation in cases with suspected eosinophilic keratoconjunctivitis [19,20] or identify neoplastic cells in cases with suspected adnexal neoplasia [21]. Keratoconjunctivitis sicca is rare in horses [22] and therefore assessment of goblet cells is of less interest in this species.…”
Section: Discussionsupporting
confidence: 83%
“…In our study, equine goblet cells were easily identified with ICS but not with CBS mirroring a previous study where few goblet cells were found with CBS and routine staining [1]. The main focus of equine conjunctival cytology is to detect and classify inflammation in cases with suspected eosinophilic keratoconjunctivitis [19,20] or identify neoplastic cells in cases with suspected adnexal neoplasia [21]. Keratoconjunctivitis sicca is rare in horses [22] and therefore assessment of goblet cells is of less interest in this species.…”
Section: Discussionsupporting
confidence: 83%
“…Garma‐Avina mentions cytology as a useful diagnostic tool, but also addresses the risk of misinterpretation. Thus, a differential diagnosis like carcinoma with squamous differentiation and papilloma should be ruled out by biopsy 27 …”
Section: Discussionmentioning
confidence: 99%
“…It accounts for 15% of skin tumors in cats but only 2% in dogs (Yager and Wilcock, 1994). A tadpole shape with a tail-like projection and keratinized blue-green hyalinized cytoplasm may be a helpful criterion in determining the cell of origin (Garma-Avina, 1994). Tumors are usually locally invasive and may metastasize to regional lymph nodes.…”
Section: Squamous Cell Carcinomamentioning
confidence: 99%